CONCEPT OF INTELLECT AND MIND IN ISLAM AND PSYCHOLOGY - Yulchiboyeva Dilfuza Ergashevna (Galaxy International Interdisciplinary Research Journal, 2023)
In this article, the concept of intellect, i.e. mind, is explained from a psychological and religious point of view. What is said about the mind in the Holy Qur’an and the definition and role of intellect in psychology are explained. The relationship between psychology and Islam is explained.